Characterization of Salmonella phage of the genus Kayfunavirus isolated from sewage infecting clinical strains of Salmonella enterica - Juliet, Ramya; Loganathan, Archana; Neeravi, Ayyanraj; Bakthavatchalam, Yamuna Devi; Veeraraghavan, Balaji; Manohar, Prasanth; Nachimuthu, Ramesh (Frontiers in Microbiology, 2024)
Salmonella is responsible for gastrointestinal diseases, and the emergence of multi-drug resistance in Salmonella is a significant issue. With over 2600 serovars in Salmonella sp., it is crucial to identify specific solutions for each serovar. Phage therapy serves as an alternate treatment option. In this study, Vb_SalP_792 phage was obtained from sewage, forming plaques in 8 out of 13 tested clinical S. enterica isolates. Transmission electron microscopy (TEM) examination revealed a T7like morphotype. The phage remains stable throughout a range of temperatures (-20 to 70 ˚C), pH levels (3-11), and in chloroform and ether. It also exhibited lytic activity within a range of MOIs from 0.0001 to 100. The life cycle revealed that 95% of the phages attached to their host within 3 minutes, followed by a 5-minute latent period, resulting in a burst size of 50 PFU/cell. The vB_SalP_792 phage genome has a dsDNA with a length of 37,281 bp and a GC content of 51%. There are 42 coding sequences (CDS), with 24 having putative functions and no resistance or virulence-related genes. The vB_SalP_792 phage significantly reduced the bacterial load in the established biofilms and also in egg whites. Thus, vB_SalP_792 phage can serve as an efficient biocontrol agent for preventing Salmonella infections in food, and its efficient lytic activity against the clinical isolates of S. enterica, sets out vB_SalP_792 phage as a successful candidate for future in vivo studies and therapeutical application against drug-resistant Salmonella infections.